Application of Problem Based Learning (PBL) Learning Model in Improving Islamic Religious Education Learning Outcomes at SDN Ditrotunan 1 Lumajang - Wardah Wardah; Moh. Sahlan; Indah Wahyuni (Electronic Journal of Education, Social Economics and Technology, 2025)
This study aims to determine the effectiveness of implementing the Problem Based Learning (PBL) model in improving student learning outcomes in Islamic Religious Education subjects at the elementary school level. The background of this research is the low level of student participation and understanding due to the use of conventional teaching methods. The research method used is classroom action research (CAR), consisting of two cycles, each consisting of planning, action implementation, observation, and reflection. The subjects of this study were fifth-grade students at SDN Ditrotunan 1 Lumajang in the 2024–2025 academic year. Data collection instruments included observation sheets, learning outcome tests, and documentation. The results showed an increase in student learning outcomes from Cycle I to Cycle II. In Cycle I, the percentage of student mastery reached 72%, which then increased to 92% in Cycle II. These findings indicate that the application of the PBL model enhances student engagement, critical thinking skills, and a deeper understanding of Islamic Religious Education material. Therefore, PBL is a feasible alternative for effective teaching strategies at the elementary level.